Activity of Hand Sanitizer Gel from Coconut Shell Liquid Smoke with a Combination Base of Galactomannan and Carbopol 940 Against Staphylococcus aureus Bacteria - Tari Putri Utami Rizki; Nilsya Febrika Zebua; Supomo; Sumardi (Jurnal Indah Sains dan Klinis, 2024)
Background: Liquid smoke acts as an antimicrobial and antioxidant, this is related to the concentration of compounds namely phenol, carbonyl and acid. Bacteria Staphylococcus aureus is classified as a gram-positive bacteria and bacteria which is commonly found on the skin, nasal passages and respiratory tract. Hands sanitizer is an antiseptic in gel form that is often used for washing hands without water. One of the natural polymers used is galactomannan. Galactomannan is a natural polymer, namely a polysaccharide isolated from seeds. The endosperm is mainly from the Arecaceae family which consists of the main chain of mannan and galactose in the side chain. Objective: Study of activity test of Hand Sanitizer Gel from coconut shell liquid smoke with a combination of galactomannan and carbopol 940 base against Staphylococcus aureus bacteria. Method: the aim of this research formulating a hand sanitizer with the active ingredient liquid shell smoke coconut can kill Staphylococcus aureus bacteria. The research was experimental with work stages including: collecting coconut shell liquid smoke, making galactomannan from palm fruit determining the concentration of coconut shell liquid smoke hand sanitizer gel, namely 0.1%, 1%, 1.5%, determining the diameter of the inhibition zone of coconut shell liquid smoke using the well method, organoleptic test, homogeneity test, pH test, spreadability test, viscosity test, preparation stability test, irritation test on volunteers and testing antibacterial activity of hand sanitizer gel preparations with liquid smoke as the active ingredient coconut shell against Staphylococcus aureus bacteria. Results: Coconut shell liquid smoke can inhibit bacterial growth Staphylococcus aureus is greatest at a concentration of 1.5%, which is equal to 12.1 mm and the coconut shell liquid smoke hand sanitizer gel preparation meets the test evaluation. Then a basic combination of galactomannan and carbopol 940 can be obtained used as a base for hand sanitizer gel because it can make hand sanitizer gel becomes thick. Conclusion: coconut shell liquid smoke can be formulated into hand sanitizer gel preparations, galactomannan can be used as a base for hand sanitizer gel